2007
DOI: 10.1097/mph.0b013e3180986e2f
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Thymic Hyperplasia in a Patient Treated for Burkitt Lymphoma

Abstract: Thymic hyperplasia results from thymic regrowth after atrophy during stressful conditions such as burns, surgery, infection, and chemotherapy. Although thymic lesions are relatively common causes of anterior mediastinal masses, they also can develop in other mediastinal compartments on rare occasions. It is well known that thymic tissue can develop in ectopic intrathoracic lesions. Few cases of ectopic thymus associated with disturbance during thymus embryogenesis have been reported as incidental findings. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The differential diagnosis of mediastinal masses after successful treatment of lymphoma consists of residual fibrosis and necrosis of the primary tumor, recurrence of disease, thymic cyst, thymic hyperplasia, pulmonary fibrosis or granulocytic sarcoma [2,4]. In the literature, CT, magnetic resonance imaging, 67 Gallium scintigraphy and 18 F-FDG PET-CT have been reported to be useful methods for the differential diagnosis of these mediastinal masses but there are limitations to each of these imaging techniques [2,5]. Thymic malignancy can be differentiated from thymoma on the basis of biologic behavior such as local invasiveness and distant metastasis (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis of mediastinal masses after successful treatment of lymphoma consists of residual fibrosis and necrosis of the primary tumor, recurrence of disease, thymic cyst, thymic hyperplasia, pulmonary fibrosis or granulocytic sarcoma [2,4]. In the literature, CT, magnetic resonance imaging, 67 Gallium scintigraphy and 18 F-FDG PET-CT have been reported to be useful methods for the differential diagnosis of these mediastinal masses but there are limitations to each of these imaging techniques [2,5]. Thymic malignancy can be differentiated from thymoma on the basis of biologic behavior such as local invasiveness and distant metastasis (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, this entity has rarely been described in older patients [1]. The occurrence of a mediastinal mass in patients following complete remission (CR) from Hodgkin's lymphoma (HL) frequently indicates relapse but some benign processes like thymic hyperplasia may present with similar features [4,5]. After CR of testicular carcinoma, thymic hyperplasia has also been reported [6].…”
Section: Introductionmentioning
confidence: 98%
“…Relapses of Burkitt's lymphoma, which most commonly occur within 6 months of completion of treatment, are associated with poor outcomes [ 1 ]. In clinical practice, remnant masses have been observed on imaging studies after completion of intensive chemotherapy in several cases [ 10 11 ]. Son et al [ 11 ] reported a case of ectopic thymic hyperplasia after chemotherapy for Burkitt's lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, remnant masses have been observed on imaging studies after completion of intensive chemotherapy in several cases [ 10 11 ]. Son et al [ 11 ] reported a case of ectopic thymic hyperplasia after chemotherapy for Burkitt's lymphoma. Karmazyn et al [ 10 ] reported 7 patients with residual abdominal masses among 33 children with abdominal Burkitt's lymphoma who were confirmed to be in complete remission after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%